Shape change of biogenic elemental selenium nanomaterials from nanospheres to nanorods decreases their colloidal stability. Issue 5 (22nd March 2017) - Jain, Rohan; Jordan, Norbert; Tsushima, Satoru; Hübner, René; Weiss, Stephan; Lens, Piet N. L.
Abstract : Microbial reduction of selenium oxyanions under mesophilic (30 °C) and thermophilic (55 °C) conditions produces biogenic elemental selenium nanospheres (BioSe-Nanospheres) and nanorods (BioSe-Nanorods), respectively. Abstract : Microbial reduction of selenium oxyanions under mesophilic (30 °C) and thermophilic (55 °C) conditions produces biogenic elemental selenium nanospheres (BioSe-Nanospheres) and nanorods (BioSe-Nanorods), respectively. While the properties of BioSe-Nanospheres are well studied, the colloidal properties of BioSe-Nanorods have not yet been investigated. Therefore, this study characterized the surface properties of BioSe-Nanorods, compared their colloidal properties with BioSe-Nanospheres and elucidated the formation of BioSe-Nanorods in the presence of a capping agent. This study demonstrated that BioSe-Nanorods, like BioSe-Nanospheres, are capped by extracellular polymeric substances (EPS) as evidenced by infrared spectroscopy. The EPS capped BioSe-Nanorods were less colloidally stable than EPS capped BioSe-Nanospheres as demonstrated by the former's less negative zeta potential values when exposed to 10 mM NaCl. In fresh lake water, BioSe-Nanospheres showed a 91.6 (±0.5)% settling efficiency, while BioSe-Nanorods displayed a settling efficiency of 97.1 (±0.5)%. The lower colloidal stability and higher settling efficiency was due to a 7 times less negative surface charge of BioSe-Nanorods compared to BioSe-Nanospheres at pH 7.2. Further, this study observed that the formation of BioSe-Nanorods might proceed via BioSe-Nanospheres through orientation attachment followed by anisotropic growth as well as a solid-solution-solid mechanism. This study demonstrates the importance of the shape of nanoparticles in determining their bioremediation effectiveness and fate in the environment.